Distorsi Teologis terhadap Inkarnasi Kristus di dalam Teori Limitasi - Elkana Chrisna Wijaya (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
This research discusses the rationale for the emergence of Christ's limitation theory, accompanied by biblical arguments, which reject the existence of the theory and criticize it from various expert opinions. The Christ limitationtheory is a theory that denies the existence of Christ who is true God and true man. Although both the divine and the human nature of Christ are the crucial points of the theory, the skepticism of his divinity is more prominent and problematic. This paper is done with a qualitative approach, using literature sources from a number of literatures. After being tested theoretically, this research draws the conclusion that the theory of the limitation of Christ has no theological and biblical foundation so it must be rejected.